Genotypic response of wheat under semi-arid conditions showed no specific responsive traits when grown under elevated CO2. (3rd July 2019) - Maphosa, Lancelot; Fitzgerald, Glenn J.; Panozzo, Joe; Partington, Debra; Walker, Cassandra; Kant, Surya
ABSTRACT: Atmospheric carbon dioxide (CO2 ) is predicted to reach 550 µmol mol −1 by 2050, increasing from the current ~410 µmol mol −1 concentration, and this will have an impact on wheat production and grain quality. Genetic differences in response to future CO2 levels, which might be exploited for higher yield and sustainable grain quality, were investigated. Twelve diverse genotypes (11 wheat lines and 1 triticale cultivar) were grown in the Australian Grains Free-Air CO2 Enrichment facility under ambient CO2 (~400 µmol mol −1 ) and elevated CO2 (eCO2 ) concentrations (550 µmol mol −1 ) in 2014 and 2015 to test for different responses to CO2 . Genotype response to eCO2 for the parameters measured showed strong linear relationships. eCO2 increased plant height (11%), aboveground biomass (31%) and grain yield (32%) as means across all genotypes. Yield response to eCO2 was driven by increases in spike number and weight. The increase in CO2 caused a mean 10% decrease in grain nitrogen content and increased grain weight by 7%. Measures of bread dough quality decreased due to eCO2 . Genotypes with large yield response did not show larger than mean reductions in grain %N. The apparent near-universal decline in grain %N under eCO2 might be compensated for by selection of genotypes that are highly responsive to increasing yields but resist dramatic declines in grain %N. Selection for responsiveness to eCO2 for yield and grain %N are likely to involve a range of co-related characteristics that balance sink and source relationships. Graphical Abstract: